2015
DOI: 10.1016/j.dr.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy-trace theory and lifespan cognitive development

Abstract: Fuzzy-trace theory (FTT) emphasizes the use of core theoretical principles, such as the verbatim-gist distinction, to predict new findings about cognitive development that are counterintuitive from the perspective of other theories or of common-sense. To the extent that such predictions are confirmed, the range of phenomena that are explained expands without increasing the complexity of the theory's assumptions. We examine research on recent examples of such predictions during four epochs of cognitive developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 185 publications
(207 reference statements)
2
75
0
2
Order By: Relevance
“…However, in the domain of Internet use, this might not necessarily be the case, as increased aged was inversely associated with experience. During healthy ageing, specific (verbatim) representations of memory decay faster and are less accessible than gist representations, and as such, older adults' increased gist reasoning in false‐recall experiments has been linked to this decay in their neurocognitive functioning (e.g., Brainerd & Reyna, ; Koustaal et al, ). In addition, Corbin et al () found that individuals with higher working memory capacity show a preference for gist reasoning strategies in risky decision making, and Huang, Wood, Berger, and Hanoch () have shown that a greater age effect exists when participants make decisions on deliberative tasks compared with experiential tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the domain of Internet use, this might not necessarily be the case, as increased aged was inversely associated with experience. During healthy ageing, specific (verbatim) representations of memory decay faster and are less accessible than gist representations, and as such, older adults' increased gist reasoning in false‐recall experiments has been linked to this decay in their neurocognitive functioning (e.g., Brainerd & Reyna, ; Koustaal et al, ). In addition, Corbin et al () found that individuals with higher working memory capacity show a preference for gist reasoning strategies in risky decision making, and Huang, Wood, Berger, and Hanoch () have shown that a greater age effect exists when participants make decisions on deliberative tasks compared with experiential tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the brain, the working brain, is a complex semantic-pragmatic processor, a meaning generator and carrier. Brainerd and Reyna 45 also make clear that essential, effective-complexity meaning is what is abstracted from contextualised semantic-pragmatic processes: what is not essential is dropped, only the gist is retained. As we mentioned and discuss later on, the schemes activated and compatible within a situation overdetermine intended performance or representation.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 99%
“…The fuzzy-trace theory 45,46 is an interesting variant of a dualprocess theory. It is interesting because its chosen dimension of variation (which has two types, gist processing versus verbatim processing) is not based on complexity, abstraction or mental effort (working memory demand), but it is instead based on meaning (deep thinking) versus the manifest signs or referents that might express simpler meaning (shallow thinking).…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…The first explanation is that false recall for visual scenes is likely to rely more on gist memory to generate theme-related lures, but children's gist memory is poorer than the other age groups. A second related explanation is that young children's language is still developing so it is harder for them to recall than recognize a thematically related lure (Brainerd & Reyna, 2015).…”
Section: Discussionmentioning
confidence: 99%